Efficacy and safety of Everolimus in children with TSC - associated epilepsy – Pilot data from an open single-center prospective study. Issue 1 (December 2016) - Samueli, Sharon; Abraham, Klaus; Dressler, Anastasia; Gröppel, Gudrun; Mühlebner-Fahrngruber, Angelika; Scholl, Theresa; Kasprian, Gregor; Laccone, Franco; Feucht, Martha
Abstract Background Epilepsy occurs in up to 90 % of all individuals with tuberous sclerosis complex (TSC). In 67 % disease onset is during childhood. In ≥ 50 % seizures are refractory to currently available treatment options. The mTOR-Inhibitor Everolimus (Votubia®) was approved for the treatment of subependymal giant cell astrocytoma (SEGA) and renal angiomyolipoma (AML) in Europe in 2011. It's anticonvulsive/antiepileptic properties are promising, but evidence is still limited. Study aim was to evaluate the efficacy and safety of Everolimus in children and adolescents with TSC-associated epilepsies. Methods Inclusion-criteria of this investigator-initiated, single-center, open, prospective study were: 1) the ascertained diagnosis of TSC; 2) age ≤ 18 years; 3) treatment indication for Votubia® according to the European Commission guidelines; 4) drug-resistant TSC-associated epilepsy, 5) prospective continuous follow-up for at least 6 months after treatment initiation and 6) informed consent to participate. Votubia® was orally administered once/day, starting with 4.5 mg/m2 and titrated to achieve blood trough concentrations between 5 and 15 ng/ml. Primary endpoint was the reduction in seizure frequency of ≥ 50 % compared to baseline. Results Fifteen patients (nine male) with a median age of six (range; 1–18) years fulfilled the inclusion criteria. 26 % (4/15) had TSC1, 66 % (10/15) had TSC2 mutations. In one patient no mutation was found. Time of observation after treatment initiation was median 22 (range; 6–50) months. At last observation, 80 % (12/15) of the patients were responders, 58 % of them (7/12) were seizure free. The overall reduction in seizure frequency was 60 % in focal seizures, 80 % in generalized tonic clonic seizures and 87 % in drop attacks. The effect of Everolimus was seen already at low doses, early after treatment initiation. Loss of efficacy over time was not observed. Transient side effects were seen in 93 % (14/15) of the patients. In no case the drug had to be withdrawn. Conclusion Everolimus seems to be an effective treatment option not only for SEGA and AML, but also for TSC-related epilepsies. Although there are potential serious side effects, treatment was tolerated well by the majority of patients, provided that patients are under close surveillance of epileptologists who are familiar with immunosuppressive agents.